“Very truly yours”: Henry W. Longfellow og den transatlantiske eksport af nordens oldskrifter og dansk romantik - Hermann, Pernille (Passage - Tidsskrift for litteratur og kritik, 2024)
“Very truly yours”: Henry W. Longfellow and the Trans-Atlantic Export of Old Norse Texts and Danish Romantic Literature This article deals with the dissemination in North America in the 19th century of Old Norse texts and Danish Romantic literary works. It argues that the American professor of literature and poet Henry W. Longfellow was an important figure in this regard. The starting point of the article is the connection between Longfellow and the Kongelige Nordiske Oldskriftselskab that was established in 1835 when Longfellow travelled to Copenhagen.